Clays and Clay Minerals, Vol. 58, No. 2, 143–153, 2010. - Boudriche, L.; Hamdi, B.; Kessaissia, Z.; Calvet, R.; Chamayou, A.; Dodds, J. A.; Balard, H. (The Clay Minerals Society, 2010)
Themost common means of reducing theparticlesizeof solids is by grinding, a process which can affect the surface properties and the behavior of the solid in later stages (granulation, compaction, etc.), and which can influence the end-use properties of the final product. Inverse gas chromatography (IGC) measurements were used here to evaluate the influence of grinding, in a ball mill, on attapulgite. The milling experiments were performed in dry media for various periods. After 30 min of grinding, significant decreases in the particle size and specific surface areas were observed when calculated using different probes. No noticeable variation in the surface properties was observed by IGC either at infinite dilution or at finite concentration, however. In particular, the distribution functions of the adsorption energies (DFAE), giving information about thesurfac ehe terogeneity for both an apolar probe(octane ) and a polar probe (isopropanol), remained unchanged, regardless of the grinding time. The stability of the surface energy with respect to the grinding process was seen to be related to the particular fibrous structure of the attapulgitec lay.
An Assessment Of The Surface Properties Of Milled Attapulgite Using Inverse Gas Chromatography
gsccm58201-bou.pdf : 735KB
Keywords: Periodicals; Geology; Adsorption Energy Distribution Functions; Attapulgite; Grinding; Inverse Gas Chromatography; Palygorskite; Surface Properties